2021
DOI: 10.14746/ssllt.2021.11.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the importance of vocabulary for English as an additional language learners’ reading comprehension

Abstract: This exploratory study represents an attempt to investigate the factors that may affect the reading comprehension abilities of English as an additional language (EAL) learners. For this study, we examined a participant group of 31 (25 EAL and 6 first language English) learners studying at an international school in Japan. We assessed the participants according to four factors shown to influence reading comprehension: vocabulary knowledge, word decoding skills, reading fluency, and general linguistic ability. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
1
23
0
2
Order By: Relevance
“…This in line with the statement said that Communicative approach helps learners to be able to contacts with others in order to talk fluency and to express about themselves confidently and to present many social issues in their environment as quick as possible (Irmawati, 2012). In addition, learners needs targeted language support to enhance academic text comprehension (Brooks et al, 2021). In document analysis and interview, it is found that in syllabus and lesson plan listed the phase of teaching method toward every topic or teaching material.…”
Section: Processsupporting
confidence: 59%
“…This in line with the statement said that Communicative approach helps learners to be able to contacts with others in order to talk fluency and to express about themselves confidently and to present many social issues in their environment as quick as possible (Irmawati, 2012). In addition, learners needs targeted language support to enhance academic text comprehension (Brooks et al, 2021). In document analysis and interview, it is found that in syllabus and lesson plan listed the phase of teaching method toward every topic or teaching material.…”
Section: Processsupporting
confidence: 59%
“…However, one or more linguistic clues can be used by the writers to address their research gap strategy such as in E6. E6 was taken from an article titled 'Exploring the importance of vocabulary for English as an additional language learners' reading comprehension' written by Brooks et al (2021) and published in Studies in Second Language Learning and Teaching, volume 11 issue 3. As indicated in E6, the writers use three linguistic features (however, despite … and … not) in addressing their research gap.…”
Section: The Linguistic Features Realizing the Research Gap Strategiesmentioning
confidence: 99%
“…A teacher added that students' obstacles in English such as vocabulary could affect students' language comprehension, especially in reading context. Some studies indicated that vocabulary mastery was important for reading comprehension and it showed a correlation (Brooks et al, 2021;Manihuruk, 2020). Moreover, critical thinking skills need the comprehension ability for analyzing until concluding.…”
Section: What Are Students' Problems In English Learning?mentioning
confidence: 99%